(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes the fact that in Ukrainian realities this problem takes on a special significance, given that the information sphere is becoming the arena of the fiercest confrontations of the democratic world with the Russian aggressor, which throughout its history tried to distort, distort, and destroy the most outstanding properties and monuments. the fabric of national history and culture. It is noted that disinformation is a fundamentally important challenge for Ukrainian statehood, as well as domestic criminology, given that disinformation and propaganda are used by the aggressor state to justify the commission of war crimes on the territory of Ukraine, to form an ideological and ideological basis for the commission of such crimes, as well as the spread of distorted social and moral beliefs that encourage individual citizens of Ukraine to collaborate. These actions of the aggressor state are aimed at leveling domestic institutions of social memory, falsification of national memory, destruction of the Ukrainian political nation, gradual "mixing" of national identity. It was emphasized that the aggressor state is trying with all its forces and available means to destroy the intellectual potential of the Ukrainian nation by attacking museums, cultural monuments and institutions of higher education. Deprived of an intellectual, ideological, cultural, creative basis, the population becomes maximally open to the influence of informational and psychological operations and disinformation. It is deep knowledge, multifaceted thinking that is the basis of media literacy. After all, disinformation strategies that saturate the political and legal space of the aggressor state seek to simplify the multifaceted nature of life as much as possible. It is argued that social initiatives, scientific projects aimed at improving the media literacy of the population, as well as the unification of leading scientists, politicians, public and creative figures around the joint understanding of problems in this field and the generation of ideas aimed at finding ways become especially important in such conditions their solution, in particular the initiative «Treason is cancelled».